Pengaruh Penggunaan Media Pembelajaran Interaktif Electronic Dictionary Card terhadap Hasil Belajar Bahasa Inggris pada Kelas VII di SMP - Saparida, Rina Aprillia; Amilia, Winanda; Yeni J, Fetri; Kurnia, Reni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is motivated by the low learning outcomes of students in the United Kingdom Subject, so the right learning media is needed to improve learning outcomes. This study aims to determine the effect of the use of Electronic Dictionary Card interactive learning media on United Kingdom learning outcomes in grade VII in junior high school. This study uses an experimental method with a pre-experiment design, especially a one group pretest-posttest design. The research sample is grading VII students of SMP Negeri 43 Mukomuko. Data collection techniques include tests, interviews, and observations, with instruments in the form of multiple-choice tests for pretest and posttest. The results of the study showed that there was a significant influence of the use of Electronic Dictionary Card interactive media on students' United Kingdom learning outcomes. This is evidenced by the increase in the average score from the pretest by 57.4 to 86 in the posttest. A simple linear regression analysis also showed the t-count value > the t-table (8.915 > 2.1009), which indicated a significant difference between the pretest and posttest results. Thus, the use of Electronic Dictionary Card interactive media has a significant effect on improving United Kingdom learning outcomes in grade VII of junior high school